2017
DOI: 10.1111/jopr.12616
|View full text |Cite
|
Sign up to set email alerts
|

The Hollow Maxillary Complete Denture: A Simple, Precise, Single‐Flask Technique Using a Caramel Spacer

Abstract: The success of removable prostheses ultimately depends on a number of factors such as retention, stability, support, esthetics, and masticatory function. Increased intraoral inter-arch distance leads to an increase in the weight of the prosthesis. This may compromise the retention and resistance, which are key for a successful removable prosthesis. Various methods, techniques, and materials have been reported to minimize the weight of a prosthesis. This article describes a simple, unique, precise single-flask … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…The benefit of using this technique is ease of handling the 3D spacer as it is solid and fixed to the denture base and retrieval is not required unlike other materials described previously 2,9,12‐19 . Also, there is no discoloration as seen in the double flask technique 1,8,11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefit of using this technique is ease of handling the 3D spacer as it is solid and fixed to the denture base and retrieval is not required unlike other materials described previously 2,9,12‐19 . Also, there is no discoloration as seen in the double flask technique 1,8,11 …”
Section: Discussionmentioning
confidence: 99%
“…The double flask technique 1,8 , 11 is technique‐sensitive as the two flasks used may not accurately fit, causing an inadvertent increase in vertical dimension. Also, the junction of the two parts of the denture may fracture, discolor or leak with time 9,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was also previously reported that the used two parts of the denture used in the procedure might discolor, fracture, or leak with time, which might reduce the efficacy and safety of the modality. 15,21 Therefore, it should be approached with caution, and considering other modalities should also be prioritized when such adverse events are suspected to maintain adequate patient safety and comfort. For performing 3D space-based procedures, many materials have been previously proposed to achieve this purpose and successfully produce a hollow cavity after the initial processing using the technique.…”
Section: Techniques Of Hollow Maxillary Denturesmentioning
confidence: 99%
“…Single denture (SD) is one of the removable appliances which attract the attention and be in mind of most of the dentists in an attempt to prolong the life of the remaining natural teeth and relating structures. The success of SD ultimately depends on a number of factors such as retention, stability, support, aesthetics, and masticatory function (1) . Construction of SD is a demanding prosthetic procedure chiefly when opposed by natural teeth in non-harmonious occlusal plane.…”
Section: Introductionmentioning
confidence: 99%